2020
DOI: 10.1111/ggi.14011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of dual sensory impairment among community‐dwelling older adults in Selangor: A secondary data analysis

Abstract: The present study aimed to examine the prevalence of dual sensory impairment, and to identify its risk factors among community-dwelling older adults in Selangor. Methods: Secondary analysis was carried out on data collected by the Grand Challenge Project among older adults aged ≥65 years from Selangor. Data on sociodemographic information, medical history, cognitive function and functional performance were obtained through face-to-face interviews using standardized questionnaires. Visual acuity was measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…The percentage of individuals with visual impairment is similar to previous studies. 17,18 However, we did not find any factors associated with visual impairment. Dyslipidemia was related to cognitive decline, and the association was also found in patients with multiple sclerosis.…”
Section: Discussioncontrasting
confidence: 82%
“…The percentage of individuals with visual impairment is similar to previous studies. 17,18 However, we did not find any factors associated with visual impairment. Dyslipidemia was related to cognitive decline, and the association was also found in patients with multiple sclerosis.…”
Section: Discussioncontrasting
confidence: 82%
“…The prevalence of vision impairment among older adults in the Selangor state of Malaysia was 27.3% [4]. More than two-thirds (76.2%) of older adults in the Selangor state of Malaysia had hearing impairment [5]. Both vision and hearing impairments can cause undesirable outcomes on physical and mental health, quality of life and cognitive function among older adults [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This prevalence is within the range of 69.9–76.2%, as reported in previous studies. 6 , 10 , 11 However, the National Health Morbidity Survey (NHMS) 2018 showed that the prevalence of self-reported hearing disability in older Malaysians aged 60 years and above was only 6.4%. 12 The marked differences in the prevalence rate between our current findings and the NHMS 2018 could be attributed to different approaches to detect hearing impairment.…”
Section: Discussionmentioning
confidence: 99%